2013
DOI: 10.3989/gya.023213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fractional crystallization on composition and thermal properties of engkabang (<i>Shorea macrophylla</i>) seed fat and cocoa butter

Abstract: RESUMENEfecto de la cristalización fraccionada sobre la composición y propiedades térmicas de grasas de semillas de engkabang (Shorea macrophylla) y de manteca de cacao Se investigan los comportamientos de una cristalización fraccionada de la manteca de cacao (CB) y la grasa de enkabang (EF) en acetona. Las muestras fundidas de CB y EF se mezclaron por separado con acetona en una relación 1:02 (w/v) y se dividen en fracciones sólida y líquida bajo condiciones de temperatura controlada. Las fracciones aisladas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A plant-based substitute for lard was proposed by Yanty et al (2017a) by making use of avocado fat as the major component and palm stearin / cocoa butter as minor components. According to a previous study by Yanty et al (2013b), Malaysian cocoa butter was found to possess POP, POS, and SOS as its major TAG molecular species. Likewise, another previously mentioned that when compared to lard, Avo of different Malaysian cultivars exhibited lower SFC values throughout the temperature range (Yanty et al, 2014a).…”
Section: Ternary Mixtures Of Avo:ps:cbmentioning
confidence: 91%
See 3 more Smart Citations
“…A plant-based substitute for lard was proposed by Yanty et al (2017a) by making use of avocado fat as the major component and palm stearin / cocoa butter as minor components. According to a previous study by Yanty et al (2013b), Malaysian cocoa butter was found to possess POP, POS, and SOS as its major TAG molecular species. Likewise, another previously mentioned that when compared to lard, Avo of different Malaysian cultivars exhibited lower SFC values throughout the temperature range (Yanty et al, 2014a).…”
Section: Ternary Mixtures Of Avo:ps:cbmentioning
confidence: 91%
“…Canola oil, a major vegetable oil, has been previously identified as a suitable candidate for novel fat formulations (Campbell et al, 2002;Marangoni and Rousseau, 1998). Several efforts have been made in the past to expand the use of EF as it is considered an under-utilized plant lipid (Yanty et al, 2013b;Nesaretnam and Mohd Ali, 1992). In a previous attempt, Gani et al (2011) demonstrated the usefulness of EF as a raw material for preparing moisturizers used in cosmetic products as well as hair conditioners.…”
Section: Binary Mixtures Of Ef:comentioning
confidence: 99%
See 2 more Smart Citations